Pendidikan Karakter dalam Islam: Analisis Filosofis Ibnu Miskawaih dalam Kitab Tahzibul Akhlak - Atika Rofiqatul Maula (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
Character education aims to direct students who have good morals. The human existence character mostly comes from the environment, such as innate, culture, and education received. Because the human character is always changed, the path is taken through the educational process, namely upbringing, and training. On the way, the student characters can experience a decrease and even deviations in space. This condition can be influenced by the environment around them. This study aims to find out how the concept of character education according to the Islamic figure, namely Ibnu Miskawaih through his book entitled "Tahdzibul Akhlak", and its relevance to education in Indonesia.This qualitative descriptive research uses content analysis technic of various documents as primary and secondary sources. In conclution, Ibn Miskawaih belongs to the Dualist-Active perspective argues that human character is built by his environment and the purpose of character education is to achieve virtue and happiness. The relevances of this topic with Indonesia education are in the subject of character and community service programs.